Investigating potential output using the Hodrick-Prescott filter: an application for Malta - Aaron G. Grech (Central Bank of Malta, 2014)
This paper, after reviewing the most used method from the two main branches of empirical investigation, namely the Hodrick-Prescott (HP) filter and the production function, argues that they both suffer from significant failings when applied to very small and open economies like Malta.
Keywords: B41; C18; E32; F41; 330